Features of the Occurrence and Development of Infectious Complications in Patients with Combat Injuries of the Musculoskeletal System (according to the Own Experience) - Hrytsai, M.P.; Poliachenko, Yu.V.; Tsokalo, V.M.; Kolov, H.B.; Yevlantieva, T.A. (TERRA ORTHOPAEDICA, 2023)
Background.  One of the characteristics of a combat injury is the penetration of pathogenic microorganisms, pieces of dirty skin, clothes, dust, etc. into the depth of the wound. The combination of significant defects of bones and soft tissues, vessels and nerves of the affected segment of the limb (musculoskeletal system) causes a high percentage of unsatisfactory treatment results, as well as the development of infectious complications.Objective: to evaluate the nature of combat wounds in patients who had  infectious complications in the musculoskeletal system during the war in Ukraine  since  2014;  to determine the features of the occurrence and development of such infectious complications.Materials and Methods. An analysis of case reports of patients with combat wounds with infectious complications (osteomyelitis, septic arthritis, surgical site infection (SSI), purulent- necrotic infection of soft tissues and wounds) who were treated at the Department of Bone- Purulent Surgery of the State Institution “Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine” for the period from 2014 to mid-2022 was carried out.Results and Conclusions. Infectious complications in combat wounds mostly arise primarily as a result of the wound itself, taking into account the severity, extent of damage to structures and tissues, the type of weapon used to inflict the injury, and a wide spectrum of microorganisms, among  which  Staphylococcus  aureus  plays  a  leading role. In the control group, infectious complications occurred more often than SSI with further progression.